Variable stiffness plate tensegrity structures inspired with topology optimization. (May 2023) - Al Sabouni-Zawadzka, Anna; Martyniuk-Sienkiewicz, Kamila; Gilewski, Wojciech
Abstract: The present study focuses on the research on modular tensegrity-based plate lattices, which are reinforced with an internal skeleton consisting of enhanced tensegrity cells. The enhanced cells that create the skeleton should have different mechanical properties than other cells of the lattice. The novel idea described in this study consists in using the results obtained from the topology optimization of various plate structures and to simulate the topologically optimal material layout in the corresponding lattice plates by using the reinforced skeleton. Three possible ways of adjusting the properties of tensegrity cells within the lattices are described: adjustment of geometric parameters, i.e. cable-to-strut stiffness ratio, adjustment of the self-equilibrated system of normal forces, and the hybrid solution. The effectiveness of the proposed techniques is demonstrated for two in-plane plate deformation tasks. Although this study focuses on large-scale plate lattices, a similar approach can also be applied to smaller scales. Highlights: Modular tensegrity-based plate lattices with reinforced skeleton are proposed. Skeleton is created from tensegrity cells of enhanced properties. Skeleton simulates optimal material layout obtained from topology optimization. In-plane deformation and plate bending are considered.